2019
DOI: 10.3892/etm.2019.7167
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen inhibits PTPRO to prevent the apoptosis of renal podocytes

Abstract: Podocytes are a major component of the glomerular filtration membrane, and their apoptosis is involved in a variety of nephrotic syndromes. In the current study, the effects and molecular mechanisms of oestrogen on the proliferation and apoptosis of podocytes were investigated to elucidate the role of oestrogen in the pathogenesis of childhood nephrotic syndrome. The cell proliferation of mouse renal podocytes (MPC-5) and human primary renal podocytes was promoted by 17β-oestradiol (E2) in what appear to be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…To explore the role of PTPRO in cancers, we first characterized the expression of PTPRO in different human tissues using the data obtained from The GTEx database ( www.gtexportal.org ) ( 19 ), via the Human Protein Atlas ( www.proteinatlas.org ). We found that PTPRO abundance was highest in the kidney ( Figure 1A ), supporting a critical physiological role of PTPRO in the kidney, as previously reported ( 7 ). Notably, all of 17 analyzed renal cancer cell lines had lower expression of PTPRO than the normal kidney tissues (MERAV database, merav.wi.mit.edu) ( 20 ) (P<0.001 for all, Figure 1B ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To explore the role of PTPRO in cancers, we first characterized the expression of PTPRO in different human tissues using the data obtained from The GTEx database ( www.gtexportal.org ) ( 19 ), via the Human Protein Atlas ( www.proteinatlas.org ). We found that PTPRO abundance was highest in the kidney ( Figure 1A ), supporting a critical physiological role of PTPRO in the kidney, as previously reported ( 7 ). Notably, all of 17 analyzed renal cancer cell lines had lower expression of PTPRO than the normal kidney tissues (MERAV database, merav.wi.mit.edu) ( 20 ) (P<0.001 for all, Figure 1B ).…”
Section: Resultssupporting
confidence: 91%
“…Protein tyrosine phosphatase receptor type O (PTPRO), a member of receptor-type PTP of the R3 subtype (4), was initially identified as a podocyte-specific protein that might regulate glomerular structure and function (7)(8)(9). PTPRO was demonstrated to participate in multiple cellular and physiological functions, including synapse formation, neuron differentiation, and podocyte proliferation (7,9,10). Recently, PTPRO has been assumed to act as a putative tumor suppressor in several cancer types (6,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous study, PTPRO aggravates atherosclerosis by promoting oxidative stress and cell apoptosis induced by oxidized low-density lipoprotein [10]. Oestrogen restricts renal podocyte apoptosis by inhibiting PTPRO [11]. Besides, PTPRO is a candidate tumor suppressor in human lung cancer and downregulation of PTPRO mediated by miR-6803-5p promotes the proliferation and invasion of the cancer cells in colorectal cancer [12,13].…”
Section: Introductionmentioning
confidence: 94%
“…For example, estrogen could increase the degradation of ECM to slow the progression of DKD through upregulating MMP-9 in MCs [ 213 ]. It also inhibited podocyte apoptosis through binding to ERβ, which was associated with the activation of the JAK2/STAT3 signaling pathway [ 214 ]. Moreover, estrogen or tamoxifen could improve albumin excretion, reduce glomerular size, and decrease matrix accumulation via upregulating the expression of ERβ and downregulating TGF-β in podocytes from db/db mice [ 215 ].…”
Section: Estrogen and Ers In Kidney Diseasesmentioning
confidence: 99%